Impact on air quality and health due to the Saddleworth Moor fire in northern England. (23rd June 2020) - Graham, A M; Pope, R J; Pringle, K P; Arnold, S; Chipperfield, M P; Conibear, L A; Butt, E W; Kiely, L; Knote, C; McQuaid, J B
Abstract: On June 24th 2018 one of the largest UK wildfires in recent history broke out on Saddleworth Moor, close to Manchester, in north-west England. Since wildfires close to large populations in the UK have been relatively small and rare in the past, there is little knowledge about the impacts. This has prevented the development of effective strategies to reduce them. This paper uses a high-resolution coupled atmospheric-chemistry model to assess the impact of the fires on particulate matter with a diameter less than 2.5 µ m (PM2.5 ) across the region and the impact on health from short-term exposure. We find that the fires substantially degraded air quality. PM2.5 concentrations increased by more than 300% in Oldham and Manchester and up to 50% in areas up to 80 km away such as Liverpool and Wigan. This led to one quarter of the population (2.9 million people) in the simulation domain (−4.9–0.7°E and 53.0–54.4°N) being exposed to moderate PM2.5 concentrations on at least one day, according to the Daily Air Quality Index (36–53 µ g m −3 ), between June 23rd and 30th 2018. This equates to 4.5 million people being exposed to PM2.5 above the WHO 24-hour guideline of 25 µ g m −3 on at least one day. Using a concentration-response function we calculate the short-term health impact, which indicates that in total over the 7-day period 28 (95% CI: 14.1–42.1) deaths were brought forward, with a mean daily excess mortality of 3.5 deaths per day (95% CI: 1.8–5.3). The excess mortalities from PM2.5 from the fires represented up to 60% of the total excess mortality (5.7 of 9.5 excess deaths), representing an increase of 3.8 excess mortalities (165% increase) compared to if there were no fires. We find the impact of mortality due to PM2.5 from the fires on the economy was also substantial (£21.1 m).